Learning organizations - Reid, Malva Daniel; Bekbalaeva, Jyldyz; Bedford, Denise; Garcia-Perez, Alexeis; Jones, Dwane (Bingley, U.K. : Emerald Publishing Limited, 2021)
The 21st century economy is fuelled by knowledge. Today, knowledge is more than an idea - it is an economic commodity. An organization's knowledge capital is a competitive and comparative advantage. Every organization must now invest in the knowledge assets of all its employees. Learning is the engine that creates and renews knowledge capital. Learning Organizations delves into why learning is an essential business operation; how modern learning is different from industrial-era training; how to discover learning sources and opportunities; how to design a learning environment and learning strategies that optimize the potential of every employee. This is essential reading for business managers, human resource professionals, and academic researchers studying knowledge economies, knowledge, and intellectual capital.
Part 1. Learing in the knowledge economy -- Chapter 1. Knowledge capital and the knowledge economy -- Chapter 2. Learning -- Chapter 3. Learning cultures -- Chapter 4. Designs for learning -- Part 2. Learning environments -- Chapter 5. Learning at the organization level -- Chapter 6. Learning at the team or group level -- Chapter 7. Learning at the individual level -- Part 3. Developing learning strategies -- Chapter 8. Designing and developing an organization-wide learning strategy -- Chapter 9. Communicating and socializing the learning strategy -- Chapter 10. Maintaining and sustaining a learning strategy.
Includes index.
Print version record.
Keywords: Organizational learning; Knowledge management; Business & Economics -- Knowledge Capital; Knowledge management